Challenges and Innovation of Indonesia Overseas Election in Tokyo - Raganata, Gusti (UI Scholars Hub, 2019)
Indonesian overseas elections were first done in 1955. However, Indonesia has lacked specific laws in regards to regulating overseas elections, with almost no distinction between overseas and domestic elections. It has barred the Overseas Election Committee (PPLN) from properly conducting simultaneous elections as well as affecting the quality of the elections. Whereas Indonesian elections are traditionally done through paper ballots in which data are collected manually, PPLNs have promoted innovations to overcome challenges. Constraints are faced by PPLN Tokyo when implementing technology-based solutions. Several of the innovations done can be studied, replicated, and applied in Indonesia’s domestic elections and can improve the quality of the elections overall.